Voice acting for dummies - Ciccarelli, David; Ciccarelli, Stephanie (John Wiley and Sons Canada, Ltd., 2013)
Voice acting is a unique career, and this guide gives you expert tips and strategies on how to succeed. From finding your signature voice and creating a demo, to auditions and booking jobs, you'll learn how to improve your vocal talents and make a career out of them.